21st Century Learning Values, Character and Moral Education in An Effort to Overcome Student's Moral Decadence - Ine Kusuma Aryani; Yuliarti Yuliarti (UM Purwokerto Press, 2023)
Starting from the rampant behavior and attitudes of moral decadence or a decline in moral values among adolescents, 21st century learning requires a theoretical study of values, character and moral education that is more comprehensive, conducive and consistent in overcoming moral decadence. Educational thinkers (including moral and charac¬ter education) such as: (1) Thomas Lickona; (2) Ki Hadjar Dewantara, and (3) Lawrence Kohlberg, define the concept of education as having different emphases, but they essentially also have the same view, namely that education emphasizes the goal of making students intellectually and morally good, national character, noble character, and carried out through a learning process with directed procedures and adequate infrastructure. By conducting qualitative research-case studies in several schools, the results obtained are that there are seve¬ral alternatives to overcome moral decadence behavior, including: a) Supervision; b) provide character education; c) law enforcement as fair as possible; d) improve religious and character education or moral or character education; e) attention from all parties, the government, the education office (in particular), practitioners, schools, especially parents of students.